Novel Immune biomarkers for the early stratification of oligoarthritis patients at risk of developing polyarticular extension - Raggi, Federica; Pelassa, Simone; Antonini, Francesca; Rossi, Chiara; Briasco, Federica; Orsi, Silvia Maria; Del Zotto, Genny; Cangelosi, Davide; Ravelli, Angelo; Gattorno, Marco; Consolaro, Alessandro; Bosco, Maria Carla (Frontiers in Immunology, 2025)
IntroductionOligoarthritis, the most common form of Juvenile Idiopathic Arthritis in Western countries and a leading cause of disability, exhibits a variable clinical course. Early identification of children at risk of polyarticular extension is critical for guiding targeted therapy, but requires new biomarkers. This study aimed at profiling T cell and monocyte/macrophage (MM) subset composition and activation/maturation state combined with extracellular vesicle (EV) surface markers in synovial fluid (SF) and peripheral blood (PB) from new-onset Oligoarthritis patients to prospectively evaluate their correlation with clinical course over a two-year follow-up period and identify potential prognostic biomarkers.MethodsSF and PB samples were collected from 42 untreated patients at disease onset. Immune cell subsets were analyzed by flow cytometry, EV marker expression profiles by bead-based multiplex assays, and soluble TREM1 (sTREM1) levels by ELLA. Differences between patients exhibiting oligoarticular course (Group 1) or polyarticular extension (Group 2) over two years of follow-up were assessed.ResultsGroup 2 patients showed significantly higher CD3:CD14 ratio (AUC = 0.831,p<0.005) and HLA-DR+ CD4+ T cell percentages (64.8%vs52.5%,p=0.02) in SF compared to Group 1 patients. In PB, both HLA-DR+CD4+ and HLA-DR+CD8+ cells were significantly increased (AUC = 0.946,p<0.001) in Group 2. Group 2 patients also exhibited significantly higher proportions of effector memory (EM) CD4+ (AUC = 0.911, p<0.001) and CD8+ (AUC:0.929, p<0.001) subsets, along with lower proportions of naïve CD4+ (AUC = 0.929, p<0.001) and CD8+ (AUC = 0.893, p<0.001) subsets in the circulation, that was reflected in a significantly higher EM:naïve ratios for both CD4+ (AUC = 0.893,p<0.001) and CD8+ (AUC = 0.946;p<0.001) populations. TREM1+ CD14+ cell percentages in both SF and PB were significantly (p<0.05) lower (SF: 83.6%vs90.47%; PB:40.16%vs53.21%), while sTREM1 levels higher (SF: 8926vs5822 pg/ml; PB:298.8vs232 pg/ml), in Group 2 compared to Group 1. Finally, SF-derived EVs from Group 2 showed significantly reduced HLA-ABC (AUC = 0.857,p=0.012) and CD3 (AUC = 0.949,p<0.001) expression. Combining these markers further improved the discriminatory performance of the models (AUC = 1,p<0.001).DiscussionThis exploratory study identifies novel immune classifiers combining T lymphocytes and MM subsets with EV markers which stratify, at onset, Oligoarthritis patients who will develop polyarticular extension and provide important mechanistic insights into arthritis progression.